Analysis of Factors Associated with Visit of Infants and Toddlers to Posyandu in Wonorejo Village, Wates Subdistrict, Kediri Regency: Analisis Faktor-faktor yang Berhubungan dengan Kunjungan Bayi dan Balita ke Posyandu di DesaWonorejo, Kecamatan Wates, KabupatenKediri - Yuliawati, Dwi; Astutik, Reni Yuli (Universitas Muhammadiyah Sidoarjo, 2020)
Posyandu provides convenience to the community in obtaining basic health services. The coverage of toddler weighing in Indonesia amounted to 71.4% in 2011 which means it has not met the target. The purpose of the research is to know the factors related to the visit of infants and toddlers to Posyandu in Wonorejo village, Wates subdistrict, Kediri regency. Design research uses correlational research design with a retrospective cohort approach. The research sample was infants and toddlers in January – October 2018 that meet the criteria of 120 people through proportional random sampling. Data collection using the data collector sheet on November 26-30, 2018. Data analysis with Chi-Square and Fisher Exact Test with a signification rate of α = 0.05. From the Chi-Square statistical test, there was a relationship between the mother's age (P = 0.043; POR = 2,911 95% CI: 1,126-7,527), mother's education (P = 0.020; POR = 0,281 95% CI: 0,102-0,774), child's age (P = 0.004; POR = 5,489 95% CI: 1,739-17,330) with infant and toddler visits to the Posyandu and from Fisher Exact test, there was a relationship between mother’s job (P = 0.029; POR = 0,290 95% CI: 0,103-0,819) with the visit of infants and toddlers to Posyandu. From the above results are known that the dominant variables associated with the visit of infants and toddlers to Posyandu is the age of the child indicating that the age of children < 24 months have a chance of 5.489 times more to the child's age ≥ 24 months.